Simulation of Robot Arm Control System by Bluetooth Using Arduino - Bagus Dwi Cahyono; Nurdayanti Nurdayanti; Nadiyah Azzahra; Dea Hardelia; Muhani Muhani (Yayasan Adra Karima Hubbi, 2024)
Era 4.0 is often referred to as the technological era. One application of technology in the industrial sector is the creation of a 4-arm robot. But in his case, 4-arm robots are rarely operated automatically. Therefore, a 4-arm robot simulation was designed using servo motors via Bluetooth. This research aims to design a 4-arm robot that is controlled using Bluetooth. The methodology used is the simulation method and literature study. The results of the simulation of a 4-arm robot controlled by Bluetooth can rotate at an angle of 45° and 90° and move automatically